Extracellular vesicles in triple-negative breast cancer: current updates, challenges and future prospects - Tiwari, Prashant Kumar; Chaudhary, Anis Ahmad; Gupta, Saurabh; Chouhan, Mandeep; Singh, Himanshu Narayan; Rustagi, Sarvesh; Khan, Salah-Ud-Din; Kumar, Sanjay (Frontiers in Molecular Biosciences, 2025)
Breast cancer (BC) remains a complex and widespread problem, affecting millions of women worldwide, Among the various subtypes of BC, triple-negative breast cancer (TNBC) is particularly challenging, representing approximately 20% of all BC cases, and the survival rate of TNBC patients is generally worse than other subtypes of BC. TNBC is a heterogeneous disease characterized by lack of expression of three receptors: estrogen (ER), progesterone (PR), and human epidermal growth factor receptor 2 (HER2), resulting conventional hormonal therapies are ineffective for its management. Despite various therapeutic approaches have been explored, but no definitive solution has been found yet for TNBC. Current treatments options are chemotherapy, immunotherapy, radiotherapy and surgery, although, these therapies have some limitations, such as the development of resistance to anti-cancer drugs, and off-target toxicity, which remain primary obstacles and significant challenges for TNBC. Several findings have shown that EVs exhibit significant therapeutic promise in many diseases, and a similar important role has been observed in various types of tumor. Studies suggest that EVs may offer a potential solution for the management of TNBC. This review highlights the multifaceted roles of EVs in TNBC, emphasizing their involvement in disease progression, diagnosis and therapeutic approach, as well as their potential as biomarkers and drug delivery.